Quantum yields of photocoloration and molar absorption coefficients of ferrocenyl substituted benzo and dibenzochromenes. Comparison with their phenyl-homologues - Pierre Brun; Robert Guglielmetti; Jean Claude Micheau; Véronique Pimienta; Stéphane Anguille (International Journal of Photoenergy)
The photochromic properties of three ferrocenyl-[2H]-benzopyrans were investigated under monochromatic irradiation and compared with those of their phenyl homologues. The UV/visible spectra of the closed and open forms are reported together with the quantum yields of photocoloration. It was shown that the ferrocenyl- substitution induces the formation of a new band in the 500–700 nm range in the open forms, however, it does not affect significantly the UV spectra of the closed forms. Ferrocenyl- substitution was also shown to increase the thermal bleaching rate constants and to decrease the photocoloration quantum yields. For most compounds, photochromic behaviour was not sensitive to the irradiation wavelength. However, for the methyl ferrocenyl chromene, the open form spectrum was slightly dependent of the irradiation wavelength. The influence of the ferrocenyl group and other structural features on the photochromic properties are discussed.